Continuous Economic Education: at Intersection of Problems - A. V. Korzhuyev (Научный диалог)
In a review of the book by T. Yu. Lomakina and M. G. Sergeyeva “Scientific bases of development of continuous economic education in the system of professional education,” published in 2015, a positive assessment of the development by the authors of theoretical and technological-methodological issues of one of the areas of continuing professional education is presented. Significance of the authors’ work for the theory and practice of vocational education is indicated.